Liturgy, Education and Cultural Resistance - Feldman, Sergio Alberto (2018)
The intention of this article understands the cultural resistance tools enabled by the Jewish minority throughout the centuries. The focus is on the religious daily life and, within it, the use of rituals and the normative precepts named mitzvot. The latter are religious commandments described in the Pentateuch ruling multiple details of religious life, from sacrifices in the Jerusalem Temple to social, conjugal, and other kinds of relationships. The analysis aims at presenting a complex web of behavioral control, which creates a minority-protecting “fence” that prevents the absorption by society and its non-Jewish majority. The analysis covers an extended time span in medieval Western Europe, using the Cultural History framework.